Pemetaan Status pH Tanah dan C-Organik Tanah Sawah Tadah Hujan di Kecamatan Panai Tengah Kabupaten Labuhanbatu - Fitra Syawal Harahap; Dedi Kurniawan; Rini Susanti (Universitas Sebelas Maret, 2021)
The production center for lowland rice in Labuhanbatu Regency in the last three years, precisely in Panai Tengah District, North Sumatra Province, has decreased production since 2018. One of the causes is a decrease in production because the nutrient content in the soil has decreased and added by fertilizer application by farmers. Lowland rice is still common due to limited data on land resources. This study aims to evaluate the land through the identification of classes, distribution and status of soil pH and C-Organic nutrients as well as organic matter in agricultural land in Central Panai District, and to determine the level of soil damage in each Land Mapping Unit. This research was carried out in Central Panai District with elevation. place 11 meters above sea level. Soil analysis was carried out in the integrated science laboratory of the Faculty of Science and Technology, Labuhanbatu University from January 2021 to March 2021, while the method in this study was a semi-detailed grid survey with the density of observation of 1 sample per 250 meters. Soil pH measurements used the pH-H2O and C-organic methods of soil using the Walkley and Black method. Furthermore, the results of the analysis of nutrient rainfed lowland soils are interpreted into a nutrient status map. The results showed that the pH content of rainfed lowland soil in Panai Tengah District, Labuhanbatu Regency was classified as very acidic and slightly acidic, while based on the soil nutrient status, namely C-organic and organic matter in the low category, so as to increase the productivity of rainfed lowland soil with soil organic matter content.up to 3% required organic fertilizer in the Central Panai District, Labuhanbatu Regency.